Phylogenetic conservation of protein-lipid motifs in pentameric ligand-gated ion channels - Barrantes, Francisco Jose (2015)
Using the crosstalk between the nicotinic acetylcholine receptor (nAChR) and its lipid microenvironment as a paradigm, this short overview analyzes the occurrence of structural motifs which appear not only to be conserved within the nAChR family and contemporary eukaryotic members of the pentameric ligand-gated ion channel (pLGIC) superfamily, but also extend to prokaryotic homologues found in bacteria. The evolutionarily conserved design is manifested in: 1) the concentric three-ring architecture of the transmembrane region, 2) the occurrence in this region of distinct lipid consensus motifs in prokaryotic and eukaryotic pLGIC and 3) the key participation of the outer TM4 ring in conveying the influence of the lipid membrane environment to the middle TM1-TM3 ring and this, in turn, to the inner TM2 channel-lining ring, which determines the ion selectivity of the channel. The preservation of these constant structural-functional features throughout such a long phylogenetic span likely points to the successful gain-of-function conferred by their early acquisition. This article is part of a Special Issue entitled: Lipid-protein interactions.